Giant Cell Tumor of The Proximal Phalanx of The Index Finger of The Hand: A Rare Case Report - Mouli Edward; Ferdiansyah Mahyudin; Muhammad Hardian Basuki; Yunus Basrewan; Caesar Haryo Bimoseno (Journal Orthopaedi and Traumatology Surabaya, 2022)
Background: Giant cell tumor (GCT) of bone is a relatively common type of benign tumor involving the epiphyseal region of tubular bones, but GCT rarely occurs at hand (1–4% of all GCT). GCT within the hand tends to be more aggressive and recurs more rapidly in hand than in other locations. Most authors prefer curettage or resection with reconstruction to maintain anatomical and functional integrity.Case Report: A 27-year-old man with a chief complaint of an enlarged lump and pain in the index finger of his left hand. These lumps appeared three months ago. Plain radiographs showed lytic, eccentric, geographic lesions with well-defined borders and narrow transition zones. Magnetic resonance imaging (MRI) showed a primary aggressive bone tumor with extension to the surrounding soft tissue. Fine Needle Aspiration Biopsy (FNAB) revealed the lesion as a Bone Giant Cell Tumor. The patient then underwent local resection and reconstruction using an allograft. Range of movement (ROM) measurements and DASH scores were evaluated.Discussion: Radiographic and MRI examinations showed characteristic cortical breach, and FNAB showed multinucleated giant cell spread. After treatment, the patient was found to be pain-free, have an improved ROM, and reduced disability. There was no recurrence observed. Conclusion: Despite the tendency for hand GCT to be more aggressive, local resection and reconstruction using an allograft with adjuvant hydrogen peroxide can reduce recurrence and disability.